The jurisdiction of the administrative judiciary in interpreting the administrative decision - a comparative study - Neama Darwish, Teacher Iqbal (The college of law and political science journal, 2023)
Interpreting the administrative decision is a judicial act that aims, in the end,to implement legality, since administrative decisions are issued based on the lawsthat regulate the work and procedures of the public administration. Interpretationis based on reaching the intended meaning of the administration’s will, and thePHDQVLQWKLVLVWKHODZVXLWWKDWLV ÀOHGHLWKHU GLUHFWO\ EHIRUHWKHDGPLQLVWUDWLYHMXGJHZLWKDQLQWHUHVWLQWKHGHFLVLRQLQTXHVWLRQRULWLVÀOHGE\MXGLFLDOUHIHUUDOIURPWKHRUGLQDU\MXGLFLDU\ZKLOHLWFRQVLGHUVDODZVXLWÀOHGEHIRUHLWRIZKDWHYHUcivil nature commercial or criminal - based on the vagueness and vagueness ofthe interested party The administrative judiciary is competent to consider the casefor interpretation, but its authority is limited to interpretation only, without goingbeyond it to the subject matter of the case, cancellation and amendment. However,the judgment issued as a result of the case has the authority of the res judicata, butit has a relative effect that does not exceed the parties to the case.